Common mistakes in multiplication and division of natural numbers among first-year students primary (Journal of the College of Basic Education, 2023)
In the period following 1958, Iraq witnessed significant development in various fields of life.economic, political, educational, cultural and other fields with the aim of removing the factorsThe backwardness that Iraq inherited from previous eras. Perhaps the most important of these fundamental transformations,The development that has been achieved in the fields of general education, and in various stages and types, especially educationIt is not surprising that primary education is the minimum level of education, in addition to being a right.Every citizen, as he is able through him to acquire knowledge of the principles of reading, writing, arithmetic, and procurement as much as possible.The school curricula provide him with knowledge and management to preserve the cultural heritage and transmit it through generations.the following. It is also considered the basis on which the other stages of education depend, and the starting point.For educational investments in the human development process for all economic and social sectors.Despite the development that took place in primary education in our country during the past years,The statistics show a high percentage of failures in the various academic subjects at different stages.Primary school. Undoubtedly, the factors for students' failure are many and varied, including the contribution ofMathematics made a significant contribution to the occurrence of this phenomenon in the primary stage.The mistakes that students make in performing the four basic operations, including multiplication and division.They are the main factors leading to the failure of quite a few students in mathematics.Therefore, the high percentage of failure is real and realistic, which raises the attention or draws the attention of those interested in issues ofeducation, and this is supported by the statistics that dealt with this main problem.primary education in Iraq, where it revealed the extent of this repetition, especially in the first gradesthe fifth and sixth primary schools. Which requires the availability of a scientific study aimed at revealing theseThe mistakes that students make when they learn these two operations, and find out the reasons that lead to them.Which may contribute to improving the method of teaching mathematics, and perhaps to making improvements to the book.school in terms of its content and arrangement in the primary school stages, thus reducing the percentage offailure in this main subject among students of this stage